Norms of Localization in Translating Persian Multimodal Texts: The case of videogame demos - Touiserkani, Farkhondeh; Afzali, Katayoon (Iranian Journal of Translation Studies, 2014)
Audiovisual translation is different from other types of translation in that in its translations, in addition to speaking content, visual aspects of an image need to be taken into consideration. Viewing this difference, the aims of the current study were threefold: 1) investigating the likely constraints of translating videogame demos, 2) investigating the norms of localization in translating videogame demos and 3) identifying the ideologies that the use of these norms indicates in the society. To this end, first, a corpus of 33 videogame demos and their Persian translations were selected and analyzed. Next, the likely constraints of translating videogame demos were specified. Then, according to Tomaszkiewich’s (1993) model and Bastin’s (2005) adaptation model, the norms of translating videogame demos were identified. Finally, what the norms of the translation of videogames showed about the ideology of the present society was recognized. The findings revealed that situational and cultural adequacy and creation in Bastin’s model are two norms most frequently used by translators. In addition to the Bastin’s model of translation strategies, two other norms, i.e. euphemism and colloquial language were recognized in translating videogame demos. The findings indicated that since the videogames have been designed for fun, they have been translated colloquially.